Determination of sertindole in biological material by gas chromatography-mass spectrometry - Davydovych, Sophia; Halkevych, Iryna; Tarnavska, Jaroslava (ScienceRise: Pharmaceutical Science, 2017)
The treatment by the new generation antipsychotic remedy Sertindole is often accompanied by QT interval prolongation accompanied and neuroleptic malignant syndrome, which often leads to fatal consequences, in case of its overdose or mixing with some other drugs. In most cases, the anatomical pathology analysis results do not give any sudden death explanation. Aim. Identification and quantitative determination of Sertindole using Gas Chromatography - Mass spectroscopy method in samples obtained after purification of the extracts from the biological material (liver) by solid-phase extraction. Methods. Sertindole was isolated from the biological material by the mixture of Acetonitrile - Perchloric acid 70% (1:1) with the following liquid extraction by 1,2-Dichloroethane (рН 11). The extracts after purification using the SPE Oasis HLB 30 mg (Waters, USA) cartridges were eluted by Ethanol 96%, evaporated to dryness under Nitrogen flow, and then the residues were dissolved in 250 μl of Methanol. Identification and assay of Sertindole in the solutions and the model samples were carried out using Agilent 6890N chromatograph equipped by 5978B Mass detector (Agilent Technology, USA), RTX-5 column was used, 30m×0,25mm, 0,25 μm (Restek, USA). Temperature gradient: 50 °С (0,5 min), 25 °С/min till 150 °С, and then the temperature rise was 10 °С/min until 320 °С was reached. Isothermal mode was set at 320 °С (30 min). Injector temperature was 270 °С. Helium was used as a carrier gas (3 ml/min). Mass detection was performed at 70 еV electronic ionization and 400V voltage. Results. At the offered conditions of the analysis Sertindole retention time was 27.79±0.05 min (RSD 0,17 %). The method is characterized by linearity within 50–200 μg/ml. It was found that Sertindole detection limit without prior derivatization in SCAN mode is 25 μg/ml. In the model samples of liver tissues Sertindole was identified and quantitatively determined. The drug detection limit in the biological material is 2 μg/g. Conclusion. Chromatographic conditions with Mass-selective detector (GC/MS) for Sertindole analysis were developed for the first time. The basic patterns of primary Sertindole fragmentation were shown. The scheme of chemical and toxicological analysis of the biological material to determine Sertindole by GC/MS method was offered. The developed method for Sertindole determination can be used in departments of forensic toxicology bureau